Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1001/archneur.62.8.1208
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Clearance of Microemboli and Cerebrovascular Symptoms During Carotid Stenting Procedures

Abstract: Background: Transcranial Doppler monitoring shows a high prevalence of microemboli during carotid artery stenting (CAS); however, the occurrence of cerebrovascular symptoms (CVSs) does not seem to be related to the microembolic load. Objective: To evaluate embolic and hemodynamic transcranial Doppler monitoring findings and their relationships with the occurrence of procedural CVSs. Patients: Fifty-four patients who had carotid stenosis of more than 70% underwent a total of 57 CAS procedures during transcrania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 16 publications
(14 reference statements)
2
27
1
3
Order By: Relevance
“…Orlandi et al recently performed TCD monitoring during carotid artery stenting and also demonstrated that MCA median blood flow velocity values at the start of the procedure were significantly lower in patients with new postoperative neurological deficits than in those without. 8 The results of our multivariate analysis correspond with this finding and support the concept proposed by Caplan and Hennerici. 6 In the present study, among patients with at least one MES during carotid dissection, MCA MFV was better than the number of MES in terms of predicting new postoperative ischemic lesions on DWI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Orlandi et al recently performed TCD monitoring during carotid artery stenting and also demonstrated that MCA median blood flow velocity values at the start of the procedure were significantly lower in patients with new postoperative neurological deficits than in those without. 8 The results of our multivariate analysis correspond with this finding and support the concept proposed by Caplan and Hennerici. 6 In the present study, among patients with at least one MES during carotid dissection, MCA MFV was better than the number of MES in terms of predicting new postoperative ischemic lesions on DWI.…”
Section: Discussionsupporting
confidence: 90%
“…Mean blood flow velocity (MFV) values were defined as diastolic flow velocity ϩone third (systolic flow velocity minus diastolic flow velocity; cm/s). 8 The MFV measured at the start of skin incision was defined as MFV during carotid dissection.…”
Section: Transcranial Doppler Monitoringmentioning
confidence: 99%
“…Endothelium has been damaged and the inflammatory process has been activated because of these microembolus. Also low perfusion pressure distal to the stenosis affects the clearence of microembolus (7). Maybe we can talk about decreasing of cerebral clearance of contrast agent with a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Further, ischemic lesions and hyperperfusion syndrome are well-known complications of CAS, and new cerebral microembolic lesions detected via diffusionweighted imaging (DWI) are observed in almost all patients after CAS (7,8). Fluid-attenuated inversion recovery (FLAIR) is very sensitive in detecting leptomeningeal hyperintensity (9), which has been noted to disappear after the symptoms resolve.…”
Section: Introductionmentioning
confidence: 99%
“…59 As recently suggested, border-zone infarcts might result from mixed mechanisms by impaired clearance of emboli in hypoperfused regions. 60 Indeed, during the constitution of the mural hematoma, only the embolic mechanism may explain the occurrence of an infarction, whereas the hemodynamic mechanism may appear progressively with the narrowing of the lumen due to the growth of the mural hematoma. Once the lumen is severely stenosed, hemodynamic impairment may encourage the formation of secondary clots in border-zone regions, impede the clearance of distal clots, and increase the impact on cerebral tissues.…”
Section: Morel Et Al Mechanism Of Ischemic Infarct In Cadmentioning
confidence: 99%